395 nm Light-Emitting Diode with 647 mW Output Power Realized Using a Double p-Type Aluminum Composition Gradient with Polarization-Induced Hole Doping. Issue 1 (2nd January 2021) - Yue, Wenkai; Li, Zhimin; Li, Peixian; Zhou, Xiaowei; Dong, Haichen; Wang, Yanli; Wu, Jinxing; Luo, Xiaoshun; Bai, Junchun
Abstract: Three p-type layer structures, i.e. a p-GaN layer, a short-period superlattice (SL) insertion layer, and a polarization-induced hole-doped double-aluminum composition gradient layer, were compared in terms of their performance in 395 nm high-power light-emitting diodes (LEDs). The device with the polarization-induced hole-doped double-aluminum composition gradient layer has an operating voltage of 3.34 V and a wall-plug efficiency of 55.3% under a 350 mA injection current. Moreover, devices with the polarization-induced hole-doped double-aluminum composition gradient layer structure have better optical output power than devices with a short-period SL inserted in p-GaN.